Analysis of the Effectiveness of Taxpayer Data Security in Implementing Tax Obligations at the Directorate General of Taxes - Novianita Rulandari; Alian Natision; Victor Van Kommer; Andri Putra Kesmawan; Suryanih Suryanih (Journal of Governance and Public Policy, 2022)
Taxpayer data security in carrying out tax obligations at the Directorate General of Taxes has experienced several problems of taxpayer data leakage because the security system is still weak, so that it is infected with malware that is able to steal taxpayers' personal data. This study aims to evaluate the effectiveness of taxpayer data security in carrying out tax obligations with case studies at the Directorate General of Taxes, knowing the obstacles faced by the Directorate General of Taxes in building a taxpayer data security information system and analyzing the efforts made by the Directorate General of Taxes regarding the development taxpayer data security system in carrying out tax obligations. This study uses a descriptive qualitative approach. Data collection techniques through observation, interviews, and documentation studies as well as data analysis techniques using content analysis. The results of this study indicate that after the taxpayer data leak occurred, the Directorate General of Taxes carried out a comprehensive system improvement so that the level of taxpayer data security became better. The participation of taxpayers in using a strong username and password is an important factor that determines the taxpayer's own data. The Directorate General of Taxes seeks to improve the security system and provide socialization to taxpayers to always use usernames and passwords that are not easily guessed and to periodically change E-filing passwords.